Altered Erythropoiesis in Mouse Models of Type 3 Hemochromatosis. (2nd May 2017) - Pellegrino, R. M.; Riondato, F.; Ferbo, L.; Boero, M.; Palmieri, A.; Osella, L.; Pollicino, P.; Miniscalco, B.; Saglio, G.; Roetto, A.
Abstract : Type 3 haemochromatosis (HFE3) is a rare genetic iron overload disease which ultimately lead to compromised organs functioning. HFE3 is caused by mutations in transferrin receptor 2 (TFR2) gene that codes for two main isoforms (Tfr2 α and Tfr2 β ). Tfr2 α is one of the hepatic regulators of iron inhibitor hepcidin. Tfr2 β is an intracellular isoform of the protein involved in the regulation of iron levels in reticuloendothelial cells. It has been recently demonstrated that Tfr2 is also involved in erythropoiesis. This study aims to further investigate Tfr2 erythropoietic role by evaluating the erythropoiesis of two Tfr2 murine models wherein either one or both of Tfr2 isoforms have been selectively silenced (Tfr2 KI and Tfr2 KO). The evaluations were performed in bone marrow and spleen, in 14 days' and 10 weeks' old mice, to assess erythropoiesis in young versus adult animals. The lack of Tfr2 α leads to macrocytosis with low reticulocyte number and increased hemoglobin values, together with an anticipation of adult BM erythropoiesis and an increased splenic erythropoiesis. On the other hand, lack of Tfr2 β (Tfr2 KI mice) causes an increased and immature splenic erythropoiesis. Taken together, these data confirm the role of Tfr2 α in modulation of erythropoiesis and of Tfr2 β in favoring iron availability for erythropoiesis.